Feedstocks influence on the process parameters and the microbial community in anaerobic digestion - Ferguson, Robert M. W. (Cranfield University, 2013)
To improve our understanding into the key parameters controlling and regulating the microbial groups involved in the anaerobic digestion (AD) process, particularly over multiple changes in operational conditions, triplicate lab-scale digesters fed with sewage sludge were exposed to single and multiple changes in organic loading rate (OLR) using either glycerol waste (a by-product of biodiesel manufacture), or Fats oils and greace (FOG waste) collected from a restaurant grease trap. For the multiple changes in OLR, digesters were either exposed to repeated addition of glycerol waste or repeated addition of both glycerol waste and FOG waste. In all conditions tested, physicochemical variables including volatile fatty acids (VFA), alkalinity, pH, biogas production and composition were analysed. Molecular fingerprint techniques including lipid and ether lipid analysis and 454-pyrosequencing of 16S rRNA genes were used to characterise the microbial communities. These techniques were chosen as they complement each other providing information on the microbial biomass and in-depth phylogenetic analysis of the microbial community, respectively. The key question addressed here was how feedstock composition and variation in OLR would affect the microbial community structure and dynamics and relate this to the performance of the digesters in terms of methane production over a long-term period (> 120 days). Multiple changes in OLR with the same feedstock resulted in faster recovery of methane production (8-10 days faster) compared to digesters exposed to single changes in OLR. This finding was associated specifically with a higher proportion of Clostridia Incertae Sedis XV (closely related to Cloacibacillus genus (83% similarity), family Synergistaceae) in the pre- exposed digesters. It is speculated that members related to Clostridia Incertae Sedis XV play an important role in the syntrophic interactions with the methanogens. Analysis of the VFA profiles supported this by showing that the higher relative abundance of Cloacibacillus was related to higher acetic acid concentrations. The pyrosequencing analysis further showed that community evenness was correlated with the best biogas methane content and shifts in specific bacterial groups was clearly correlated with digester performance. Overall the findings of this PhD provide new insights into the relationships between microbial community structure and digester performance. It also provides new-evidence based knowledge on how molecular microbiological tools can be used in the future to optimise and manage AD plants.